Assessing the phytosanitary threats of two non-native crickets under temperature change - Anna K. Kulessa; Ross N. Cuthbert; Ismael Soto; Paride Balzani; Mathieu Toutain; Antonín Kouba; Phillip J. Haubrock (Journal of Pest Science, 2025)
Numerous phytosanitary threats challenge global agriculture, ecosystems, and food security. These threats are exacerbated by non-native species and diseases that are projected to intensify in the future due to global warming and anthropogenic habitat alterations. Assessments of the ecological impacts of overlooked phytosanitary threats are urgently needed under shifting environments. In this study, the potential effects of two non-native Orthoptera species (the house cricket Acheta domesticus and the two-spotted cricket Gryllus bimaculatus ) were assessed using functional response analyses. We quantified their potential impacts on agriculturally relevant crops (millet) under increasing temperatures (20 °C, 25 °C, and 30 °C) as individuals and between interspecific pairs. The experiments revealed similar impacts on seeds between both species and across temperatures. Temperature tended to amplify consumption rates and functional responses. The combined interspecific cricket presence generally yielded an additive effect on seeds, with a few instances of synergistic interactions, whereby non-trophic interaction strengths significantly interacted with resource density and temperature. Both species demonstrated remarkable adaptability to varying temperatures, with low mortality accentuating their capacity for impacts under current and future temperatures. This emphasizes the imperative of including both species in phytosanitary assessments. Moreover, population monitoring and the implementation of effective management strategies emerge as pivotal measures for safeguarding agricultural productivity and conserving local ecosystems in the future. The study’s findings thus underscore the potential impact of A. domesticus and G. bimaculatus , particularly in the context of steadily ascending temperatures, to pose a risk to agricultural productivity and food security.

Correction to: Assessing the phytosanitary threats of two non-native crickets under temperature change - Anna K. Kulessa; Ross N. Cuthbert; Ismael Soto; Paride Balzani; Mathieu Toutain; Antonín Kouba; Phillip J. Haubrock (Journal of Pest Science, 2025)

Ecological importance of crayfish claws in consumption of mobile benthic prey - Mathieu Toutain; Ismael Soto; Francisco J. Oficialdegui; Paride Balzani; Ross N. Cuthbert; Phillip J. Haubrock; Antonín Kouba (Aquatic Sciences, 2024)

Assessing the role of non-native species and artificial water bodies on the trophic and functional niche of Mediterranean freshwater fish communities - Mathieu Toutain; Nadège Belouard; David Renault; Phillip J. Haubrock; Irmak Kurtul; Sadi Aksu; Özgür Emiroğlu; Antonín Kouba; Ali Serhan Tarkan; Paride Balzani (Science of The Total Environment, 2024)

Biological invasions are a population‐level rather than a species‐level phenomenon - Phillip J. Haubrock; Ismael Soto; Danish A. Ahmed; Ali R. Ansari; Ali Serhan Tarkan; Irmak Kurtul; Rafael L. Macêdo; Adrián Lázaro‐Lobo; Mathieu Toutain; Ben Parker; Dagmara Błońska; Simone Guareschi; et al. (Global Change Biology, 2024)
Biological invasions pose a rapidly expanding threat to the persistence, functioning and service provisioning of ecosystems globally, and to socio‐economic interests. The stages of successful invasions are driven by the same mechanism that underlies adaptive changes across species in general—via natural selection on intraspecific variation in traits that influence survival and reproductive performance (i.e., fitness). Surprisingly, however, the rapid progress in the field of invasion science has resulted in a predominance of species‐level approaches (such as deny lists), often irrespective of natural selection theory, local adaptation and other population‐level processes that govern successful invasions. To address these issues, we analyse non‐native species dynamics at the population level by employing a database of European freshwater macroinvertebrate time series, to investigate spreading speed, abundance dynamics and impact assessments among populations. Our findings reveal substantial variability in spreading speed and abundance trends within and between macroinvertebrate species across biogeographic regions, indicating that levels of invasiveness and impact differ markedly. Discrepancies and inconsistencies among species‐level risk screenings and real population‐level data were also identified, highlighting the inherent challenges in accurately assessing population‐level effects through species‐level assessments. In recognition of the importance of population‐level assessments, we urge a shift in invasive species management frameworks, which should account for the dynamics of different populations and their environmental context. Adopting an adaptive, region‐specific and population‐focused approach is imperative, considering the diverse ecological contexts and varying degrees of susceptibility. Such an approach could improve and refine risk assessments while promoting mechanistic understandings of risks and impacts, thereby enabling the development of more effective conservation and management strategies.

Assessing the potential phytosanitary threat of the house cricket Acheta domesticus - Anna K. Kulessa; Paride Balzani; Ismael Soto; Mathieu Toutain; Phillip J. Haubrock; Antonín Kouba (Science of The Total Environment, 2024)

Discrepancies between non-native and invasive species classifications - Phillip J. Haubrock; Ross N. Cuthbert; Paride Balzani; Elizabeta Briski; Carlos Cano-Barbacil; Vanessa De Santis; Emma J. Hudgins; Antonín Kouba; Rafael L. Macêdo; Melina Kourantidou; David Renault; Axel E. Rico-Sánchez; et al. (Biological Invasions, 2024)

Tracking long-term shifts in non-native freshwater macroinvertebrates across three European countries - Mathieu Toutain; Ismael Soto; Jes Jessen Rasmussen; Zoltán Csabai; Gábor Várbíró; John F. Murphy; Paride Balzani; Antonín Kouba; David Renault; Phillip J. Haubrock (Science of The Total Environment, 2024)